ERROR ANALYSIS ON NARRATIVE PARAGRAPHS OF THE SIXTH GRADE STUDENTS OF MA’ARIF INNOVATIVE ELEMENTARY SCHOOL - AHDA, RIZKA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: error analysis, error, narrative paragraphs, Ma’arif Innovative Elementary School.English nowadays becomes the primary language of instruction in journal and students’ textbook of the scientific, technological, and academic information. Considering the importance of English, Indonesians are expected to learn Englishearnestly. However, it is not easy to learn English as a foreign language since during the learning process, the first language of learners’ influences them. In this study Error Analysis is chosen to analyse narrative paragraphs written by Ma’arif Innovative Elementary School’s sixth grade students. This study aims to identify  the types of errors and the most frequent errors found in the narrative paragraphs of sixth grade students of Ma’arif Innovative Elementary School.This study is qualitative in the form of document analysis. The data are 15 test papers of narrative paragraphs produced by sixth grade students from the superior class at Ma’arif Innovative Elementary School. The analysis of error is based on Surface Strategy Taxonomy theory proposed by Dulay et al. (1982).The result of this research is that the students produced errors in their narrative paragraphs. Those are misformations (Mf), which are the most frequent errors produced with 83 errors (60%), omissions (Om) with 40 errors (29%), additions (Ad) with 12 errors (9%), and misordering (Md) with 3 errors (2%).The conclusion of this research is that the errors appeared at every students’ test paper in which those represent all four types of errors based on the Surface Strategy Taxonomy. The researcher realises that during the process of foreign language learning, the students were influenced by their first language because of interlanguage. Suggestion is made for the next researchers to conduct similar research with different object such as articles in the internet as the data source.